2019
DOI: 10.1002/jcb.29509
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator activated receptor γ promotes mineralization and differentiation in cementoblasts via inhibiting Wnt/β‐catenin signaling pathway

Abstract: Peroxisome proliferator activated receptor γ (PPARγ) is a member of the nuclear receptor family of transcription factors, which involved in inflammation regulating and bone remodeling. Rare studies explored the effects of PPARγ on mineralization and differentiation in cementoblasts. To explore the potential approaches to repair the damaged periodontal tissues especially for cementum, the present study aims to investigate the effects and the regulating mechanism of PPARγ on mineralization and differentiation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…24,25 Moreover, our previous studies have demonstrated that activated WNT/β-catenin signalling and accumulation of β-catenin in the nucleus could inhibit mineralization in ameloblasts and cementoblasts. 26,28 In the present study, we found increased translocation of β-catenin into the nucleus and reduced differentiation activity in ALC-Per2-sh cells. Meanwhile, overexpression of PPARγ partially rescued the inhibited differentiation activity in ALC-Per2-sh cells, which was characterized by enhanced AKT1 and β-catenin phosphorylation levels, decreased expression of β-catenin in the nucleus and increased ALP staining and ALP activity in the ALC-Per2-sh-pEnCMV-Pparγ group.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…24,25 Moreover, our previous studies have demonstrated that activated WNT/β-catenin signalling and accumulation of β-catenin in the nucleus could inhibit mineralization in ameloblasts and cementoblasts. 26,28 In the present study, we found increased translocation of β-catenin into the nucleus and reduced differentiation activity in ALC-Per2-sh cells. Meanwhile, overexpression of PPARγ partially rescued the inhibited differentiation activity in ALC-Per2-sh cells, which was characterized by enhanced AKT1 and β-catenin phosphorylation levels, decreased expression of β-catenin in the nucleus and increased ALP staining and ALP activity in the ALC-Per2-sh-pEnCMV-Pparγ group.…”
Section: Discussionsupporting
confidence: 61%
“…PPARγ was reported to participate in AKT phosphorylation and β-catenin regulation. 21,27,28 Here, we found that the mandibular first molar germs of circadian disturbance mice exhibited reduced protein expression of BMAL1 (Supplemental Fig. S2a), PER2, PPARγ and AMELX (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…The markers of macrophages have also been shown to diversely affect cementoblast mineralization. The M1 polarization markers IL-1β, IL-6, and TNF-α were observed to attenuate the mineralization of cementoblasts, while the M2 polarization marker PPARγ was suggested to be a promoter of cementoblast mineralization [14][15][16][17]. In the present study, we examined the effect of macrophages with different polar-ization phenotypes on the mineralization of cementoblasts.…”
Section: Discussionmentioning
confidence: 91%
“…On that basis, Li et al conducted in vitro experiments to demonstrate that M2-polarized macrophages could enhance the cementoblastic differentiation of periodontal ligament stem cells [13]. Further explorative experiments found that the M1 polarization markers IL-1β, IL-6, and TNF-α could attenuate the mineralization of cementoblasts, while the M2 polarization marker PPARγ promoted cementoblast mineralization [14][15][16][17]. These results all suggested a potential linkage between macrophages, cementoblasts, and root resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt signaling is putatively involved in various developmental processes such as skeletal development and tooth formation (Hu et al, 2019;Wang et al, 2019). It has been shown in various report that canonical Wnt signaling is activated during osteogenic differentiation in human bone marrow mesenchymal stem cells (BMMSCs) (Matsushita et al, 2020;Xiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%